Media Interaktif Pengenalan Karakter Wayang Pandawa, Metode Talking Stick Pada Siswa Kelas III SD Negeri Jatisari Semarang - Erria Dilasetiara; Fitro Nur Hakim (Universitas PGRI Semarang, 2018)
Based on the results of observation, the learning method used in SD N Jatisari Semarang is in the form of discourse, discussions, question and answer with the book media. Learning methods that have been applied so far have not had enough impact on students' level of understanding. The method used is less successful, so students feel bored and bored. This study uses the concept of interactive media, the